A new dynamic programming algorithm to workspiece sort problem - Xusong, Xu; Dacheng, Liu; Jing, Lu (Wuhan University journal of natural sciences, 1997)
This paper provides a new dynamic programming algorithm for solving workpiese sort problem This algorithm sort set of n workpieces in the calculating time of O(n).